Behavioral Specificities Indicating Pupils’Talent in the Three First Levels of Primary School According the Theory of Effective Intelligence from the Viewpoint of Their teachers (ExploratoryStudy in Ouarglacity) - حابي حليمة (Milev Journal of Research and Studies, 2020)
The present study aimed to prospect for talented pupils at the three levels in primary classes inOuargla on the basis of significant behavioral features, under the light of the successful intelligence theory from their teacher‘viewpoint .The following variants have been considered: sex, educational level school knowledge in relation with the behavioral features significant of giftedness.The descriptive method have been followed, and the study gaved the following results: -The ratio of pupils presenting the behavioral features significant of giftedness from the teachers’ viewpoint, according to the successful intelligence theory 23.78%. -There are no statistically significant differences in the behavioral features of the pupils presenting the features of giftedness in connection with sex. -There are statistically significant differences pupils presenting the behavioral features significant of giftedness in connection with class level (first year-second year-third year) in favor of the third year. -There is no statistically Signiant among the importance of the behavioral features and the importance of school learning among the pupils presenting the features of giftedness. The results have been discussed in the light of earlier studies and the study concluded with a number recommendations